Osing Language as Cultural Heritage: Challenges and Efforts - Putri, Raisha Anindhita; Putri, Intan Melani Putri; Zakpri, Haikal Wa’fiq (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
This study explores the preservation of the Osing language in Banyuwangi, Indonesia, which faces significant threats from globalization and the dominance of foreign languages. The research aims to identify the challenges faced by the Osing language, particularly among the younger generation, and to propose effective strategies for its preservation. Utilizing qualitative methods, including interviews and literature reviews, the findings reveal a decline in the use of the Osing language due to urbanization and cultural shifts. The study highlights the importance of local education, cultural festivals, and social media in raising awareness and fostering the use of the Osing language among youth. This research contributes to the understanding of language preservation as a vital aspect of cultural identity